Pengaruh nilai tambah ekonomi, utang keuangan dan ukuran perusahaan terhadap profitabilitas perusahaan - M. Puspitasari, Devy; F. Permana, Resti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine the development of each economic added value variable, financial debt, firm size, and profitability, as well as to determine both partially or simultaneously each economic added value variable, financial debt, firm size, and profitability in pharmaceutical industry companies that are registered in the IDX for the 2013-2020 period. The first descriptive method is used by researchers, followed by a quantitative verification method. Researchers use secondary data. The sample used was an annual report for eight periods (2013–2020) of four sub-sector companies. Where the total total samper was 32 samples. The design of the analysis implemented in this study starts with the multiple linear regression analysis, then the classical assumption test, the analysis of the coefficients of determination and correlation, and a hypothesis test using SPSS software. The study's findings show that, while economic added value and firm size have a partially negative but not statistically significant effect on ROE, financial debt has a partially positive and statistically significant effect. While simultaneously examining the three independent variables (economic added value, financial debt, and firm size), the results indicate a positive and significant influence on the profitability of the pharmaceutical industry.